The King of Kings - Sosin, Donald; Tikker, Timothy J.; Riesenfeld, Hugo (Criterion, 2004)
Cecil B. DeMille made his mark as one of cinema’s most prolific showmen early on his career. Though his name would later become synonymous with the big scale Technicolor Biblical epics of the 50s, it was during the 20s that he honed his skill and indulged his lavish sense of style and scale to the works of the Holy Texts. Long before Charlton Heston parted the Red Sea under his direction, he had successfully tried the trick in the 1920s, and long before many of his contemporaries were bringing the story of Jesus of Nazareth to the big screen, DeMille had beaten them to the punch with "The King of Kings". [www.dvdmoviecentral.com]
Keywords: DVD-Video